Metabolism and Mechanism of Human Cytochrome P450 Enzyme 1A2 - Guo, Jingchao; Zhu, Xiaohui; Badawy, Sara; Ihsan, Awais; Liu, Zhenli; Xie, Changqing; Wang, Xu (Current drug metabolism, 2021)
Human cytochrome P450 enzyme 1A2 (CYP1A2) is one of the most important cytochrome P450 (CYP) enzymes in the liver, accounting for 13% to 15% of hepatic CYP enzymes. CYP1A2 metabolises many clinical drugs, such as phenacetin, caffeine, clozapine, tacrine, propranolol, and mexiletine. CYP1A2 also metabolises certain precarcinogens such as aflatoxins, mycotoxins, nitrosamines, and endogenous substances such as steroids. The regulation of CYP1A2 is influenced by many factors. The transcription of CYP1A2 involves not only the aromatic hydrocarbon receptor pathway but also many additional transcription factors, and CYP1A2 expression may be affected by transcription coactivators and compression factors. Degradation of CYP1A2 mRNA and protein, alternative splicing, RNA stability, regulatory microRNAs, and DNA methylation are also known to affect the regulation of CYP1A2. Many factors can lead to changes in the activity of CYP1A2. Smoking, polycyclic aromatic hydrocarbon ingestion, and certain drugs (e.g., omeprazole) increase its activity, while many clinical drugs such as theophylline, fluvoxamine, quinolone antibiotics, verapamil, cimetidine, and oral contraceptives can inhibit CYP1A2 activity. Here, we review the drugs metabolised by CYP1A2, the metabolic mechanism of CYP1A2, and various factors that influence CYP1A2 metabolism. The metabolic mechanism of CYP1A2 is of great significance in the development of personalised medicine and CYP1A2 target-based drugs.